2022
DOI: 10.1108/ijchm-08-2021-1025
|View full text |Cite
|
Sign up to set email alerts
|

Does Michelin effect exist? An empirical study on the effects of Michelin stars

Abstract: Purpose Receiving Michelin stars is considered an effective marketing tool and a prestigious certification in the restaurant industry. However, the direct effects of Michelin stars on restaurant performance remain unclear. To bridge this gap, this study aims to empirically validate the “Michelin effect” on the consumption values of restaurant patrons before and after receiving Michelin stars. Design/methodology/approach The data, collected from OpenTable, consist of over 160,000 reviews written for 218 resta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…For instance, Kiatkawsin and Han (2019) found that gastronomic involvement significantly impacts consumers' willingness to pay a premium price at Michelin-starred restaurants. In a study by Bang et al. (2022) that examined the “Michelin effect” on customer consumption values, it was discovered that Michelin stars enhance nonfunctional values such as social engagement, hedonic experiences and service excellence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Kiatkawsin and Han (2019) found that gastronomic involvement significantly impacts consumers' willingness to pay a premium price at Michelin-starred restaurants. In a study by Bang et al. (2022) that examined the “Michelin effect” on customer consumption values, it was discovered that Michelin stars enhance nonfunctional values such as social engagement, hedonic experiences and service excellence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Kiatkawsin and Han (2019) found that gastronomic involvement significantly impacts consumers' willingness to pay a premium price at Michelin-starred restaurants. In a study by Bang et al (2022) that examined the "Michelin effect" on customer consumption values, it was discovered that Michelin stars enhance nonfunctional values such as social engagement, hedonic experiences and service excellence. Vargas-Sanchez and L opez-Guzm an (2022) investigated the creative process in Michelin-starred restaurants in Spain, revealing a correlation between gourmet experiences, the chef's personality, the restaurant's business model and overall success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Michelin Guide is regarded as a tastemaker of contemporary food and restaurant culture, wielding both symbolic and material power in the global restaurant industry [35,36]. MSRs are usually positioned as fine-dining restaurants which offer high-quality food, innovative menus beyond the norm, pricing that is expensive compared to casual restaurants, and social status and self-expression values when consumed [37].…”
Section: Michelin-starred Restaurants and Sustainabilitymentioning
confidence: 99%
“…As nostalgia is widely discussed as an emotional state triggered by wishful longing for a personally experienced past (Kim et al , 2019), researchers have mostly focused on examining the influence of nostalgic stimuli on emotions (Hwang and Hyun, 2013; Song et al , 2021). However, some researchers have argued that customers’ cognitive evaluations, such as perceived benefits, perceived value and familiarity, are important determinants of restaurant patrons’ future behaviors (Bang et al , 2022; Jang, 2021). Thus, the lack of investigation on the effect of nostalgia stimuli on customers’ perceived value and familiarity indicates a significant research gap.…”
Section: Introductionmentioning
confidence: 99%